Sustaining University-Community Engagement Activities in Malaysian Higher Education Institutions - Md. Yunus, Aida Suraya; Shuib, Munir; Masron, Tarmiji; Abdul Rahim, Asyirah; Azman, Norzaini; Abdul Rahman, Shukran; ,; , (PENERBIT UNIVERSITI SAINS MALAYSIA (Universiti Sains Malaysia, Penerbit Universiti Sai), 2019)
University-community engagement is essential for a nation’s economic and social future. Despite the emphasis on the essentiality of university-community engagement, extent of Malaysian academics involvement in these programmes has not been as encouraging as their commitment to research and teaching. This study was a descriptive exploratory study, with the purpose of describing the data and characteristics of university-community engagement in Malaysian higher education institutions. The intention was to provide baseline data by gathering facts through surveys, individual interviews, focus group discussions and analysing secondary data. Various interrelated aspects of university community engagement in higher education institutions were explored to provide directions in drawing recommendations for university-community engagement in Malaysia. In this study, types of university-community engagement activities was classified as (i) service, (ii) outreach, (iii) partnership, and (iv) curricular. Levels of involvement that were determined are informing, consulting, involving, collaborating and lastly, empowering the community which was based on the model of engagement developed by the International Association for Public Participation to demonstrate the possible types of engagement and the increasing level of public impact as one progresses from ‘inform’ to ‘empower’. Geographical distribution was identified using the following classifications: (i) Local/state, (ii) National and (iii) International. Based on the findings, nine strategies have been identified in promoting university community engagement in Malaysian HEIs, which includes establishment of National University-Community Framework; introduction of Critical Agenda Project (CAP) for University-Community Engagement; realigning research agenda to meet community needs; and establishing monitoring and evaluation mechanism for University-Community Engagement.